1995
DOI: 10.1007/bf01027078
|View full text |Cite
|
Sign up to set email alerts
|

Marginal cost and second-best pricing for water services

Abstract: Marginal costs, second-best (ramsey) pricing, translog multiproduct cost function,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 7 publications
0
26
1
Order By: Relevance
“…His findings suggest that prices charged to residential customers are too low that they amount to only one third of the estimated marginal cost for water supply. Kim (1995) investigated the U.S water utilities by regarding the utilities as multi-product firm for "residential" and "non-residential" services and examined the pricing strategy of water services relative to marginal cost and second-best pricing. Results confirmed that the pricing structure and the marginal cost are quite different while the second best optimum is quite close to the then existing pricing structure.…”
Section: Zef Discussion Papers On Development Policy 129 6 2 Previousmentioning
confidence: 99%
See 1 more Smart Citation
“…His findings suggest that prices charged to residential customers are too low that they amount to only one third of the estimated marginal cost for water supply. Kim (1995) investigated the U.S water utilities by regarding the utilities as multi-product firm for "residential" and "non-residential" services and examined the pricing strategy of water services relative to marginal cost and second-best pricing. Results confirmed that the pricing structure and the marginal cost are quite different while the second best optimum is quite close to the then existing pricing structure.…”
Section: Zef Discussion Papers On Development Policy 129 6 2 Previousmentioning
confidence: 99%
“…Furthermore, it does not require a priori the assumptions of homotheticity, separability, neutrality, constant returns to scale or unitary elasticities of substitution. In this study, following many other studies (Christensen and Greene, 1976;Babin et al, 1982;Renzetti, 1992;Kim, 1995;Fabbri and Fraquelli, 2000;Garcia and Thomas, 2001), the translog cost function is employed.…”
Section: Zef Discussion Papers On Development Policy 129 8 3 Theoretimentioning
confidence: 99%
“…The questions addressed are varied and numerous. Hirshleifer et al, 1960Ryordan, 1971Dandy et al, 1984Zarnikau, 1994Chambouleyron, 2003 Seasonal or temporal variations Gisy and Loucks, 1971Riley and Scherer, 1979Manning and Gallagher, 1982Dandy et al, 1984Zarnikau, 1994Elnaboulsi, 2001Schuck and Green, 2002 Capacity constraints or expansion decisions (Peak-load pricing) Hirshleifer et al, 1960Ryordan, 1971Gysi and Loucks, 1971Riley and Scherer, 1979Manning and Gallagher, 1982Zarnikau, 1994Elnaboulsi, 2001 Griffin, 2001 Scarcity Moncur and Pollock, 1988Zarnikau, 1994Elnaboulsi, 2001Griffin, 2001Schuck and Green, 2002 Revenue requirements Hirshleifer et al, 1960Freedman, 1986Collinge, 1992Zarnikau, 1994Kim, 1995Griffin, 2001Schuck and Green, 2002 Optimal number of metered connections Barrett and Sinclair, 1999Griffin, 2001Chambouleyron, 2003 Efficiency of block tariffs Gisy andLoucks, 1971 Elnaboulsi, 2001 Second-best pricing Kim, 1995Elnaboulsi, 2001Schuck and Green, 2002 Optimal derivation of nonlinear pricing schemes Elnaboulsi, 2001 Customer heterogeneity ...…”
Section: Water Pricing Modelsmentioning
confidence: 99%
“…Three main specific purposes can be found in the relevant empirical literature. One is to evaluate price schemes and to design optimal prices (Garcia-Valiñas, 2005;Garcia and Reynaud, 2004;Kim, 1995;Renzetti, 1992). Another is to analyse the effects of ownership and regulation on utility performance (Saal and Parker, 2000;Bhattacharyya et al, 1995;Feigenbaum and Teeples, 1983).…”
mentioning
confidence: 99%